Progress in treatment and outcome for children with neonatal haemochromatosis. Issue 2 (1st March 2003) - Flynn, D M; Mohan, N; McKiernan, P; Beath, S; Buckels, J; Mayer, D; Kelly, D A
Abstract : Aim: To evaluate the role of antioxidant treatment and liver transplantation in the management of neonatal haemochromatosis. Methods: A retrospective review was performed of eight infants with acute liver failure and raised ferritin levels between 1990 and 1998. From 1994, treatment with an antioxidant cocktail (vitamin E, N -acetylcysteine, selenium, prostaglandin E1, and desferrioxamine) was begun once the diagnosis was suspected. Pathological and other findings were reviewed, and outcome before and after antioxidant treatment was evaluated. Results: Median age at presentation was 4 days with median ferritin levels of 4180 μg/l (range 1650–40 000 μg/l; normal range 110–503 μg/l). Three infants presented before 1994. One infant died before liver transplantation from acute liver failure and one from neurological damage after transplantation. The third patient underwent successful transplantation at day 13 and remains well on follow up 8 years later. From 1994, five patients received antioxidant treatment, of whom two responded: both responders started antioxidants earlier (by day 5) than non-responders and had lower peak ferritin levels (< 4200 μg/l) and a milder phenotype. Treatment was continued until ferritin levels were < 500 μg/l. Both children remain well with mean follow up of 42 months, with no recurrence of iron overload. One child showed a partial response to treatment and survived long enough for a liver transplant, but died from graft failure after the transplant. Two children did not respond to antioxidant treatment; both had multiorgan failure and were not listed for transplantation. Only three of the eight patients survived (37.5%) over this time period. Conclusion: Neonatal haemochromatosis can be a fatal disease with > 60% mortality. Early treatment with antioxidant cocktail is beneficial and may be curative in those who present with milder phenotype. Liver transplantation should always be considered at an early stage in non-responders and in children with more severe acute liver failure.